176 The Levels of GFAP and UCH-L1 During the First Week After a Traumatic Brain Injury—Correlations With Clinical and Imaging Findings and Outcome. (August 2015) - Posti, Jussi; Takala, Riikka; Runtti, Hilkka; Newcombe, Virginia; Outtrim, Joanne; Katila, Ari; Frantzén, Janek; Ala-Seppälä, Henna; Coles, Jonathan; Hossain, Iftakher; Kyllönen, Anna; Maanpää, Henna-Riikka; et al.
Abstract : INTRODUCTION: Astrocyte-specific glial fibrillary acidic protein (GFAP) and neuron-specific ubiquitin C-terminal hydrolase-L1 (UCH-L1) are biomarkers, which may help to detect traumatic brain injury (TBI), assess its severity, and improve outcome prediction. We investigated the relation of the GFAP and UCH-L1 levels to the severity of TBI and their prognostic value during the first week after the injury. METHODS: Serum UCH-L1 and GFAP were measured from 389 consecutive patients with acute TBI and 81 controls enrolled in a multicenter prospective study (TBIcare). The measures included initial Glasgow Coma Scale (GCS), head computed tomography (CT) scan, and blood samples (admission and on days 1, 2, 3, and 7). The outcome was assessed using the Glasgow Outcome Scale (GOS) or its extended version (GOSe). RESULTS: GFAP and UCH-L1 levels on admission and during the first 2 days after the injury correlated with the initial GCS. In addition, UCH-L1 levels on the seventh day correlated with the initial GCS. On admission, AUC (receiver operating characteristics) of biomarkers for distinguishing any pathological finding in CT was 0.739 and 0.621, for GFAP and UCH-L1, respectively. There was a negative correlation with the outcome and UCH-L1 and GFAP levels on the first 3 and 2 days, respectively. UCH-L1 and GFAP distinguished patients with GOS 1 to 3 from patients with GOS 4 to 5. For UCH-L1 to predict unfavorable outcome (GOS < 4), incomplete recovery (GOSe < 8), or death, the AUC was 0.727, 0.538, and 0.655, respectively. For GFAP the corresponding AUCs were 0.723, 0.628, and 0.716, respectively. CONCLUSION: These results support the prior findings of the potential role of GFAP and UCH-L1 in acute phase and prognostic diagnostics of TBI. The novel finding is that GFAP and UCH-L1 levels correlated with the initial severity of TBI during the first 2 days after the injury, thus enabling a window for TBI diagnostics with latency.